The Algorithmic Horizon: Charting the Next Generation of Telemedicine Platforms - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The Algorithmic Horizon: Charting the Next Generation of Telemedicine Platforms The landscape of healthcare is undergoing a profound transformation, dri...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics